INFLUENCE OF QUALITATIVE TRAITS ON ZOOMETRIC CHARACTERISTICS OF DONKEYS IN NORTH WEST NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Qualitative and zoometrical traits were used to determine the relationship among Red (Auraki), Black (Duni), White (Fari), Brown (Idabari) and Brown-white (Idabari-fari) donkeys at different ages. A total of 700 donkeys were used for the study. Zoometric measures taken were body weight, head length, head width, ear length, neck length, neck circumference, shoulder width, height at withers, heart girth, body length and tail length. The qualitative data were collected on hair type, skin colour, skin type, coat colour pattern, tail shape, eye colour and head profile. Data obtained were subjected to statistical analysis system (SAS) to determine the distribution of phenotypic traits. Analysis of variance were used to determine the effect of various qualitative factors on zoometric indices. Significant variations were observed between qualitative (P
Keywords: Qualitative traits, Zoometric characteristics, Donkeys, Nigeria.